Plan de alimentación escolar - Collaguazo Chiguano, Sandra Carolina (2017)
The purpose of this research is to analyze how the feeding plan affects the academic performance of students of the Eighth year of General Basic Education of the “Mejía D7” School located in the province of Pichincha, Quito Canton, Quitumbe parish, Pueblo solo Pueblo neighborhood in the academic year 2016-1017?, this work aims to carry out a diagnostic evaluation of the school feeding plan, through bibliographical and trends of research to establish the incidence of poor academic performance due to malnutrition. For this reason, this work will include the influence of the school feeding plan on academic performance in order to strengthen the teaching-learning process. This field research will help to know the importance of feeding in education, in this way the social importance of the present research is evidenced, helping to deepen the aspects that integrate the inquiry into its objectives and the beneficiaries in their welfare, granting relevance to the research. The scientific method will allow getting information to make the corresponding diagnosis on the subject, in addition the field research will use to know statistical data about the incidence of the problem....